Su'ubatul Thalabah Fii Fahmi Al-Lughah Al-Arabiyah bii Madrasah Tsanawiyah Muhammadiyah Al-Mihniyah Malang - Nisa’ Urrahmah; Supriyansyah; Uril Bahruddin (Shaut al Arabiyyah, 2023)
In general, every student often has difficulty in learning. The are various of difficulties faced by students especially in learning Arabic. This study intends to discover the difficulties experienced by students in learning Arabic at SMK Muhammadiyah 2 Malang. This study used a descriptive qualitative approach at SMK Muhammadiyah 2 Malang, East Java, Indonesia. The participants of this study are the Arabic teachers and students of SMK Muhammadiyah 2 Malang class XI obtained through interviews via WhattsApp. Data were analyzed through three stages, namely reduction, presentation and verification of data. Finally, the data validation technique used data triangulation and sources.The results of this study indicate that there are three main topics in identifying students' difficulties in learning Arabic, namely the forms of difficulties in learning Arabic, the factors that make it difficult to understand Arabic learning and the impact of the difficulties in understanding Arabic learning for students of XI SMK Muhammadiyah two Malang